2008
DOI: 10.1177/117762500800200003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor Polymorphisms with Asthma in Tunisian Children

Abstract: Background: Previous studies demonstrated that the vascular endothelial growth factor (VEGF) was being implicated in the airways infl ammation and remodeling process in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…In the promoter region of the VEGF gene, we found no significant difference between the asthma and control groups, although rs699947 has been reported to be associated with VEGF plasma level, pre-school lung function, and lung cancer risk (Kreiner-Møller et al, 2013;Fan et al, 2015), and the G allele of rs2010963 has been reported to be associated with asthma (Lachheb et al, 2008). These differences probably result from disparities in the sample sizes, populations, and clinical phenotypes.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the promoter region of the VEGF gene, we found no significant difference between the asthma and control groups, although rs699947 has been reported to be associated with VEGF plasma level, pre-school lung function, and lung cancer risk (Kreiner-Møller et al, 2013;Fan et al, 2015), and the G allele of rs2010963 has been reported to be associated with asthma (Lachheb et al, 2008). These differences probably result from disparities in the sample sizes, populations, and clinical phenotypes.…”
Section: Discussioncontrasting
confidence: 51%
“…We found that the T allele in the asthma group was present in a significantly higher proportion than in the control group. The VEGF rs3025039 SNP is not only associated with asthma (Lachheb et al, 2008); like the VEGF rs3025020 polymorphism, rs3025039 is also associated with other diseases, for example, bisphosphonate-related osteonecrosis of the jaw (Choi et al, 2015) and ovarian cancers (Janardhan et al, 2015). Compared with healthy controls, the frequency of the T allele of rs3025039 is significantly higher in patients with HCH (He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the -2549 I/D polymorphism in the context of susceptibility to various diseases like Behcet's disease (BD) (Salvarani et al, 2004), asthma (Lachheb et al, 2008), HCC (He et al, 2010), recurrent miscarriages (Aggarwal et al, 2011), and end-stage renal disease (Prakash et al, 2012). Association of the DD genotype of the -2549 I/D polymorphism has been reported with diabetic retinopathy (Awata et al, 2002;Buraczynska et al, 2007), diabetic nephropathy (Yang et al, 2003), peripheral artery disease (Bleda et al, 2012), and end-stage renal disease (Prakash et al, 2012).…”
mentioning
confidence: 99%
“…All asthmatics and controls were genotyped using polymerase chain reaction (PCR) following Lachheb et al [22] for the verification of the presence of the VEGF polymorphism, which comprises the addition or the loss of 18 base pairs (18 bp) within the promoter region at position -2549 -2567. The concentration of the isolated DNA and its purity were identified using a spectrophotometer (NanoDrop, Thermo…”
Section: Genotyping Of the Vegf Polymorphismmentioning
confidence: 99%